2013
DOI: 10.1242/jeb.094219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of running on human Achilles tendon length-tension properties in the free and gastrocnemius components

Abstract: SUMMARYThe elastic properties of the human Achilles tendon are important for locomotion; however, in vitro tests suggest that repeated cyclic contractions lead to tendon fatigue -an increase in length in response to stress applied. In vivo experiments have not, however, demonstrated mechanical fatigue in the Achilles tendon, possibly due to the limitations of using two-dimensional ultrasound imaging to assess tendon strain. This study used freehand three-dimensional ultrasound (3DUS) to determine whether the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
62
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 36 publications
16
62
2
Order By: Relevance
“…Effect of exercise on Achilles free tendon transverse morphology at rest Consistent with previous in vivo studies, we found no change in regional CSA measured at rest immediately after exercise (Burgess et al, 2009;Farris et al, 2012;Lichtwark et al, 2013;Obst et al, 2015;Ooi et al, 2015). While our results did show a small but consistent reduction in CSA across all measurement regions (∼7%), post hoc comparisons failed to reveal any significant differences between time points at any of the tendon regions.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Effect of exercise on Achilles free tendon transverse morphology at rest Consistent with previous in vivo studies, we found no change in regional CSA measured at rest immediately after exercise (Burgess et al, 2009;Farris et al, 2012;Lichtwark et al, 2013;Obst et al, 2015;Ooi et al, 2015). While our results did show a small but consistent reduction in CSA across all measurement regions (∼7%), post hoc comparisons failed to reveal any significant differences between time points at any of the tendon regions.…”
supporting
confidence: 89%
“…All 3DUS calibration, acquisition and image segmentation procedures were performed using the Stradwin software package (Stradwin 4.7 1 , Cambridge University, UK; http://mi.eng.cam.ac.uk/∼rwp/stradwin/). Previous work has established the accuracy and repeatability of freehand 3DUS for in vivo measurement of human muscle morphology (length and volume) at rest (Barber et al, 2009) and Achilles free tendon morphology (length, volume, CSA, AP diameter and ML diameter) under passive and active loading conditions (Lichtwark et al, 2013;Obst et al, 2014aObst et al, ,b, 2015.…”
Section: Dus Measurement Of Achilles Free Tendon Mechanical and Morpmentioning
confidence: 99%
See 2 more Smart Citations
“…The most likely explanation for this observation is that the pain experienced during the contact phase of the SSC can trigger inhibition of neuromuscular activity 21 resulting in delays or reductions in EMG activity 9 . Alternatively, it is possible that the earlier offsets observed are a manifestation of a learnt behaviour, adopted in response to chronic changes in muscular performance or alterations in sensory input secondary to changes in tendon compliance 22 Some methodological issues require consideration. The descriptive nature of this study limits causative interpretations; it is not possible to elucidate the temporal relationship between altered SSC behaviour, AT symptoms and pathology.…”
Section: Discussionmentioning
confidence: 99%